Automation for Robotics - Jaulin, Luc, 1967- (London, UK : ISTE Ltd ; Hoboken, NJ : John Wiley and Sons, Inc., 2015)
A discipline that is in full development, propelled by the rise of autonomous mobile robotics - notably drones - automation has the objective of designing controls capable of working within an existing dynamic system (automobile, airplane, economic system, etc.). The resulting controlled system is thus constructed by looping a physical system activated and equipped with sensors using smart electronics. While the initial system only obeyed the laws of physics, the evolution of the looped system also obeyed an IT program embedded in the control electronics. In order to enable a better understa.
3.2.2. Transfer function3.2.3. Laplace transform; 3.2.4. Input-output relation; 3.3. Relationship between state and transfer representations; 3.4. Exercises; 3.5. Solutions; 4: Linear Control; 4.1. Controllability and observability; 4.2. State feedback control; 4.3. Output feedback control; 4.4. Summary; 4.5. Exercises; 4.6. Solutions; 5: Linearized Control; 5.1. Linearization; 5.1.1. Linearization of a function; 5.1.2. Linearization of a dynamic system; 5.1.3. Linearization around an operating point; 5.2. Stabilization of a nonlinear system; 5.3. Exercises; 5.4. Solutions; Bibliography
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Automatic control; Robotics; TECHNOLOGY & ENGINEERING / Engineering (General); Automatic control; Robotics; Robotics -- Technology and innovations; Robotics; Robots; Electronic books